THE IMPACT OF THE PRINCIPLE OF SEPARATION OF POWERS ON THE DEVELOPMENT OF COMMON LAW AND THE PROTECTION OF THE RAPE VICTIMS’ RIGHTS - Temba Maseko (Obiter, 2022)
The importance of protecting and promoting human rights has, over the years, received enormous support in our legal system. Everyone, including our courts, is tasked, in one way or another, with the responsibility to protect and advance human rights, including those of the rape victim. Normally, the courts protect rape victims’ rights by determining whether their rights have been violated, and if so, will order the guilty party to, among other things, compensate the rape victim. The courts also protect the rape victims’ rights by developing common law where it does not comply with the spirit, purport and object of the Constitution of the Republic of South Africa, 1996 (hereinafter “the Constitution”). When developing common law to protect rape victims’ rights, the courts are required to respect and protect the principle of separation of powers which entails the division of state power between the legislature, the executive and the judiciary. The legislature is responsible for drafting the laws, the executive is tasked with implementing the law and the judiciary is tasked with interpreting the law. The court must guard against interfering with the powers of the legislature or the executive when developing the common law. The courts have developed the common law in order to protect human rights on many occasions. This note discusses two cases in which common law was developed to protect the rape victims’ rights and it also analyses the impact of the principle of separation of powers upon the protection of their rights. Those cases are: K v Minister of Safety and Security (2005 9 BCLR 835 (CC)) and Masiya v Director of Public Prosecution (2007 8 BCLR 827 (CC)). The first part of this note analyses these cases with particular reference to the development of common law to protect rape victims’ rights. The second part discusses the development of common law and the protection of rape victims’ rights in these cases. The third part analyses the impact of the principle of separation of powers in these cases, on the development of common law in order to protect rape victims’ rights. The fourth and the last part discusses the standard test that will assist the courts to develop the common law in order to protect the rape victims’ rights, without interfering with the powers of the legislature.